A Software Tool to Support the Selection of Candidates in Private Security Services - Moricova, Valeria; Vaclavkova, Monika; Studena, Jana; Wang, Bo (Communications - Scientific letters of the University of Zilina, 2018)
Nowadays the protection of life, health and property of individuals is in the centre of public interest. There is not a distinction between the provision of such protection by private or public sector. The private security services play an important role in protection of persons and property. The subjects of protection are not only people and property, but also sensitive information which is relevant for the state interest or business entities. Based on research, the private security services do not make a selection of employees systematically. One of the reasons is the absence of an analysis of candidates’ personal competencies which should take into account the requirements of the protected subject. The aim of the article is therefore a software solution for modelling the personal competencies of applicants for the job in private security services.